S.T.S. dan Masalah Diagnose Syphilis - Perpustakaan UGM, i-lib ([Yogyakarta] : Universitas Gadjah Mada, 1974)
The Wassermann, Kahn and VDRL reactions are usually done routinely. A diagnosis based sorely on STS reaction is not recommended, although all of the three reactions are positive, moreover a diagnosis based only on one positive STS reaction is of small significant without clinical diagnosis and history of suspected syphilis. Non-specific STS is better for routine testing and for screening, as it is more sensitive while specific STS is better for solving diagnostic problems. Arti singkatan-singkatan yang dipakai : CWR = Cardiolipin Wassermann Reaction VDRL = Veneral Disease Research Laboratory RPR = Rapid Plasma Reagin RPCF = Reiter Protein Complement Fixation KRPA = Kolmer with Reiter Protein Antigen TCF = Treponema pallidum Complement â¢ Fixation T C P = Treponema pallidum Cryolysis Protein TPA = Treponema pallidum Agglutination TPHA = Treponema pallidurn aem-Agglutination TPI Treponema pallidum Immobilization FTA Fluorescent Treponemal Antibody ABS = Absorption